Assessing the reliability and validity of knowledge, attitude, and practice (KAP) assessments on COVID-19 transmission knowledge and preventive measures among ecotourism operators - Kaderi, Mohd Arifin; Zainuddin, Norafiza; Saad, Nurulwahida; Ismail, Hazmal; Hanafiah, Mohd Hafiz; Mior Shariffuddin, Nur Shahirah (Malaysian Institute of Planners, 2024)
This cross-sectional study conducted in rural Pahang state, Malaysia, aimed to validate a questionnaire examining ecotourism operators’ Knowledge, Attitude, and Practice (KAP) regarding COVID-19 transmission and preventive measures. Data collection utilised the snowball technique. The questionnaire, comprising 34 items covering knowledge, attitude, and practice constructs, underwent rigorous validation and piloting before the actual fieldwork. All factor loading scores (>0.65) and Cronbach’s alpha (α≥0.69) were greater than the reference value, relaying indicators of reliability and internal consistency of the measured latent variables. The findings revealed that the KAP model met the goodness-of fit criteria (HTMT<.90, SRMR<0.08, NFI>0.90) and convergent validity was achieved (AVF≤0.50). The study confirms the meticulous instrument validation, ensuring the survey tool’s effectiveness in gauging KAP among ecotourism operators. This study’s novelty lies in its focus on the KAP spectrum vis-à-vis COVID-19 among operators engaged in these ecotourism domains. By bridging this gap, the research aspires to inform tailored interventions, ultimately fortifying resilience against future health crises in ecotourism communities.